Preparation of TiO2 Superhydrophobic Composite Coating and Studies on Corrosion Resistance - Zhou, Chaogang; Chen, Qiya; Chen, Qinggong; Yin, Huawei; Wang, Shuhuan; Hu, Chuanbo (Frontiers in Chemistry, 2022)
The superhydrophobic coatings with excellent performance are prepared on the brass substrate to improve its application limitations in real production. In this article, the superhydrophobicity was obtained by the modification of TiO2 nanoparticles, and the FAS/STA-TiO2 superhydrophobic coating of the composite structure was obtained by modification of 1, 1, 2H, 2H-perfluoroquine trimethyl silane (FAS). By using scanning electron microscopes (SEMs), X-ray spectrometers (EDSs), and Fourier transform infrared (FTIR) spectrometers, the surface morphology, chemical composition, and functional group structure of the samples were analyzed in turn. Experiments show that the water contact angle of the FAS-modified STA-TiO2 coating reaches 161.3°, and the sliding angle is close to 1.2°. Based on the chalk dust containment, it has enabled noticeable self-cleaning properties. The composite superhydrophobic coating also presents enhanced adhesive strength compared with the single coating by the tape peeling experiment. Moreover, the composite coating has a corrosion current density as low as 8.41 × 10-7 A/cm2, and the largest |Z| in low frequency in a 3.5% NaCl solution to achieve better protection of the brass substrate. It is also not difficult to see that FAS/STA-TiO2 coating can not only improve the corrosion resistance of brass substrates but also be applied to other metal substrates.